1991
DOI: 10.1002/ddr.430220310
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic effects of a novel Na+ and Ca++ channel blocker, SD‐3212: A comparison with its enantiomer (SD‐3211)

Abstract: Miyawaki, N., F. Yamazaki, T. Furuta, T. Shigei, and H. Yamauchi: Antiarrhythmic effects of a novel Na' and Ca++ channel blocker, SD-3212: A comparison with its enantiomer (SD-3211). Drug Dev. Res. 22:293-298, 1991. The electrophysiological and antiarrhythmic effects of a structurally novel compound, SD-3212, were evaluated in comparison with its enantiomer (SD-3211). In isolated guinea pig ventricular muscles, SD-3212 reduced the maximum upstroke velocity and the plateau phase of action potential in a conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…The antiarrhythmic action of the drug has been attributed to its sodium and calcium channel blocking properties from the profiles of the antiarrhythmic effect (Miyawaki et al, 1991;Nagashima et al, 1992;Hirasawa et al, 1992). SD-3212 was shown to be effective against various experimental arrhythmias such as those induced by ouabain-, chlorform, two-stage coronary ligation, and halothane plus adrenaline (Fukuchi et al, 1990;Miyawaki et al, 1991;Nagashima et al, 1992). In terms of the class I effect of SD-3212, two reports have indicated that SD-3212 inhibits P.,.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiarrhythmic action of the drug has been attributed to its sodium and calcium channel blocking properties from the profiles of the antiarrhythmic effect (Miyawaki et al, 1991;Nagashima et al, 1992;Hirasawa et al, 1992). SD-3212 was shown to be effective against various experimental arrhythmias such as those induced by ouabain-, chlorform, two-stage coronary ligation, and halothane plus adrenaline (Fukuchi et al, 1990;Miyawaki et al, 1991;Nagashima et al, 1992). In terms of the class I effect of SD-3212, two reports have indicated that SD-3212 inhibits P.,.…”
Section: Resultsmentioning
confidence: 99%
“…This agent is reported to possess antiarrhythmic properties with vasodilator action (Miyawaki et al, 1991;Nagashima et al, 1992;Hirasawa et al, 1992). In experimental animals, SD-3212 exerted a potent and long-lasting inhibitory action against ventricular tachyarrhythmias induced by chloroform, ouabain, adrenaline and ischaemia/reperfusion (Fukuchi et al, 1990;Miyawaki et al, 1991;Nagashima et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The calcium antagonistic action of SD-3212 in vascular smooth muscle was shown to be less potent (approximately one tenth) than that of SD-3211 (Nakayama et al, 1992). In experiments on cardiac muscle, (1 -10 pM), unlike SD-321 1, decreased the maximum upstroke velocity (Vma) of the action potential in a concentration-dependent manner (Miyawaki et al, 1991). In Langendorff-perfused rabbit hearts, caused an inhibition of atrio-ventricular conduction with comparable prolongation of atrio His bundle (AH) and His bundleventricular (HV) intervals (unpublished data).…”
mentioning
confidence: 92%
“…This compound is a stereoisomer of semotiadil fumarate (SD-3211), a recently developed non-dihydropyridine type calcium antagonist (Miyawaki et al, 1990;Fukuchi et al, 1990;Teramoto, 1993). In vitro and in vivo experiments on rats, guinea-pigs, and dogs, showed that SD-3212 had a potent and long lasting inhibitory or protective action against ventricular tachyarrhythmias induced by chloroform, ouabain, adrenaline, coronary occlusion and reperfusion (Fukuchi et al, 1990;Miyawaki et al, 1991;Nagashima et al, 1992). The antiarrhythmic potency of SD-3212 in these animal models is appreciably higher than that of SD-3211.…”
mentioning
confidence: 99%
“…Semotiadil (R-isomer) is a new calcium antagonist with a non-dihydropyridine structure [25][26][27][28][29] , and shows antihypertensive 30,31 and antianginal activities. 32,33 Levosemotiadil (S-isomer) is an antiar-rhythmic drug with sodium and calcium channel-blocking action [34][35][36][37][38][39] , as well as potassium-blocking activity. 40 Both enantiomers are highly bound to plasma proteins, and their unbound concentrations could not be determined precisely using any conventional methods.…”
Section: -3mentioning
confidence: 99%